PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DENGAN AUTHENTIC ASSESSMENT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PADA MATERI LUAS PERMUKAAN DAN VOLUME LIMAS SISWA KELAS VIIID MTsN ARJASA JEMBER - Hussen, Saddam; Sugiarti, Titik; Susanto, S (Department of Mathematics Education , University of Jember, 2014)
Abstract. The Using of unsuitable learning model will result unoptimal learning. To avoid this, the teacher should be careful enough in selecting and using learning models, especially involve students actively. The result of information obtained from interviews with mathematic teacher, the assessment carried out based on one test only. This research was conducted to improve the grade VIII D student’s learning achievement and their active participation through the implication of Student Team Achievement Division (STAD) method of cooperative learning type with authentic assessment on the surface area and volume of the pyramid at MTsN 1 Arjasa in the 2012/2013 academic year. The research design was Classroom Action Research (CAR), and the data collecting methods were observation, test, interview, and documentation. From the actions implemented in each cycle, it was proved that the students’ score improved from 66,65 in Cycle 1, to 78,94 in Cycle II. Thus, the average percentage of the second cycle was 83,33% and it fulfilled the research criteria, it showed that the implication of STAD can improve the students’ learning achievment and their active participation. Key Words : STAD, authentic assessment, surface area, volume, pyramid